Comparative analysis of spatial genetic structures in sympatric populations of two riparian plants, Saxifraga acerifolia and Saxifraga fortunei. Issue 4 (21st April 2021) - Magota, Kana; Sakaguchi, Shota; Hirota, Shun K.; Tsunamoto, Yoshihiro; Suyama, Yoshihisa; Akai, Kensei; Setoguchi, Hiroaki
Abstract : Premise: The genetic structure between plant populations is facilitated by the spatial population arrangement and limited dispersal of seed and pollen. Saxifraga acerifolia, a local endemic species in Japan, is a habitat specialist that is confined to waterfalls in riparian environments. Its sister species, Saxifraga fortunei, is a generalist that is widely distributed along riverbanks. Here, we examined sympatric populations of the two Saxifraga species to test whether the differences in habitat preference and colonization process influenced regional and local genetic structures. Methods: To reveal genetic structures, we examined chloroplast microsatellite variations and genome‐wide nucleotide polymorphisms obtained by genotyping by sequencing. We also estimated the gene flow among and within populations and performed landscape genetic analyses to evaluate seed and pollen movement and the extent of genetic isolation related to geographic distance and/or habitat differences. Results: We found strong genetic structure in the specialist S. acerifolia, even on a small spatial scale (<1 km part); each population on a different waterfall in one river system had a completely different predominant haplotype. By contrast, the generalist S. fortunei showed no clear genetic differentiation. Conclusions: Our findings suggest that the level of genetic isolation was increased in S . acerifolia by the spatially fragmented habitat and limited seed and pollen dispersal over waterfalls. Habitat differentiation between the sister taxa could have contributed to the different patterns of gene flow and then shaped the contrasting genetic structures.